Mitochondrial DNA haplogroups are associated with severe sepsis and mortality in patients who underwent major surgery. Issue 1 (January 2015) - Jiménez-Sousa, Maria Angeles; Tamayo, Eduardo; Guzmán-Fulgencio, María; Heredia, María; Fernández-Rodríguez, Amanda; Gómez, Esther; Almansa, Raquel; Gómez-Herreras, José I.; García-Álvarez, Mónica; Gutiérrez-Junco, Sandra; Bermejo-Martin, Jesús F.; Resino, Salvador; et al.
Summary Objective To analyse whether mitochondrial DNA (mtDNA) haplogroups are associated with severe sepsis and mortality after major surgery. Methods We performed a case-control study on 240 cardiac or abdominal surgery patients developing severe sepsis (Case-group) and 267 cardiac or abdominal surgery patients without severe sepsis and with systemic inflammatory response syndrome (SIRS, Control-group). Furthermore, a longitudinal substudy was performed for analysing the survival in septic patients. Only European white patients within the N macro-cluster were included. Results Case-group underwent cardiac surgery had lower frequencies of cluster HV (p = 0.005) and haplogroup H (p = 0.005) and higher frequencies of cluster JT (p = 0.028) than Control-group; but no significant differences were found for abdominal surgery. Besides, both cluster HV and haplogroup H were associated with decreased odds of severe sepsis (adjusted odds ratio (aOR) = 0.45 (95%CI = 0.25; 0.82); p = 0.009 and aOR = 0.48 (95%CI = 0.26; 0.87); p = 0.015, respectively) among patients underwent cardiac surgery. In Case-group, 45.4% (109/240) patients died with a survival median of 39 (95%CI = 31.4; 46.62) days. When the clusters were examined, 41% (55/134) patients within cluster HV died versus 71.4% (10/14) patients within cluster IWX (p = 0.018). Additionally, patients within cluster IWX had an increased risk of death (adjusted hazard ratio (aHR) = 2.22; (95%CI = 1.14; 4.34); p = 0.019). Conclusions European mitochondrial haplogroups might be related to the onset of severe sepsis in patients who underwent major cardiac surgery, but not in patients underwent major abdominal surgery. Besides, mtDNA haplogroups could have influence on mortality in septic patients.